1
$\begingroup$

In terms of finding the sum of the series $\sum_{n=5}^{\infty} \frac{6}{n^2 - 3n}$ , this series looks to me like it is telescoping. So, I tried to factor it in a way to find a telescoping pattern, but I was unable to.

$\endgroup$
  • $\begingroup$ Have you tried partial fractions, then telescoping? $\endgroup$ – Kenny Wong Jun 1 '18 at 21:10
  • $\begingroup$ This is indeed telesoping through partial fraction decomposition (PFD first of course). Why don't you show us what you did before a ton of people are going to answer this for you? $\endgroup$ – imranfat Jun 1 '18 at 21:10
8
$\begingroup$

$\dfrac{6}{n(n-3)} = \dfrac{A}{n}+\dfrac{B}{n-3}$

$A(n-3) +Bn = 6$

$A = -2, B = 2$

This gives you:

$$\sum_{n=5}^\infty \left( \dfrac{2}{n-3}-\dfrac{2}{n} \right)$$

$\endgroup$
  • $\begingroup$ $=2\left(\sum_{n=2}^{\infty}\frac{1}{n}-\sum_{n=5}^{\infty}\frac{1}{n}\right)=2\left(\frac{1}{2}+\frac{1}{3}+\frac{1}{4}\right)$ $\endgroup$ – Cesareo Jun 1 '18 at 22:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.